South African agricultural productivity in the global context: Comparisons using FAO data - Arndt, Channing; Nin-Pratt, Alejandro (United Nations University, 2020)
This paper seeks to address the following questions: (a) How productive is South Africa’s agricultural sector? (b) How does it compare to other countries in terms of productivity? The approach taken uses neoclassical growth accounting in defining total factor productivity (TFP) growth as the ratio of output and input growth. There are three distinctive periods in the performance of South Africa’s agricultural sector. The first period, from 1961 to 1980-1981, is one of sustained growth in output driven by growth in input. TFP remains stagnant during this period. The second period, between 1981 and 1994 is characterized by a decreased trend in the use of inputs and by a large drop in output in 1982 followed by a period of output growth and recovery. In 1991, and after almost ten years of growth, however, output was only reaching its 1981 level. During this period, output growth and recovery is driven by TFP. The last period, starting in 1995–1996 is one of accelerated growth in output and TFP and the end of decline in aggregated input, which reverts the trend of the previous two decades and started a period of growth. Relative to other countries, growth in TFP was rapid in South Africa from 1995–2004 (3.4 percent, which was fastest of all comparator countries). After 2005, it has been relatively slow (1.5 percent) compared to other countries and compared to the previous period. Relative to the global production possibilities frontier (PPF), South African agriculture has been approaching the global PPF. Efficiency, as measured by proximity to the global PPF, improved from 0.66 from 1981 to 1994 to 0.81 in 1995-2004 and to 0.88 in 2005-2014. Overall, South African agriculture is reasonably productive in terms of TFP and has been approaching the global PPF. However, productivity growth slowed in the most recent period, 2005-2014, pointing to a need for efforts to identify the sources of the slowdown and address them.